Overlooked benefits and services of grasslands to support policy reform - Louhaichi M.; Clifton K.; Kassam S.N.; Werner J. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Despite their ecological, economic and social importance, Mediterranean grasslands continue to receive limited scientific, political and media attention. Grasslands are typically viewed as underutilized space, able to be transformed into more “valuable” land by placing it under cultivation, transforming it into forest land and/or privatizing it. This paper synthesizes a number of pertinent issues in relation to social and economic systems on grasslands within the southern Mediterranean region. One effective avenue for drawing more attention to the need for preserving grasslands is to emphasize the economic aspects and benefits of grasslands, relative to the costs of degradation and the cost of inaction. This paper defines marketable and non-marketable goods that are not clearly defined in the literature of sustainable grassland management. When goods are clearly defined payment for environmental services is feasible. Providing an enabling environment for community-based land use and decision-making may foster an acceptance of schemes for community-based payment for ecosystem services on grasslands. There is a need for policies which provide security in property rights, risk reducing strategies, and that take into account both technical and socioeconomic constraints to ensure adequate incentives for participation in grassland management. This is important as mismanagement and climate change have led to further degradation. Land tenure practices and improper policies can also act as indirect drivers of grassland degradation. When farmers and herders lose control or long-term security over the land they use, the incentives for maintain environmentally sustainable practices are lost.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)